Peningkatan Kapasitas Kelompok Tani Jaya Makmur Kurik Merauke melalui Pelatihan Pembuatan Asap Cair Sekam Padi sebagai Biopestisida Organik - Maria Magdalena Diana Widiastuti; Yosefina Mangera; Andriyono Andriyono; Jamaludin Jamaludin; Nurhening Yuniekowati (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2020)
Farmers ussually using chemical pesticides and mostly ignore the recommended dosage, chemical pesticides used spend 20% of analysis farming bussiness and food saftey become neglected for increasing production. The purpose of community capacity building is to increase farmers knowledge of making liquid smoke from agricultural waste rice husk as biopesticides for farmer groups in Kampung Jaya Makmur, Merauke Regency. The method of this empowerment by training and mentoring the process of liquid smoke production and assist the process of marketing liquid smoke products. The results of community service were the modifications of kiln drum (biochar maker) belong to farmer group into a liquid smoke maker using the pyrolysis method. This tool has been trial process and trained to farmers group of Jaya Makmur. The training of process of liquid smoke was attended by 26 farmers, 2 pioneer farmers, 3 students, and 9 lecturers from the Faculty of Agriculture and the Faculty of Engineering Musamus University. The capacity building was followed by assisting program for biochar and liquid smoke production and calculating operational costs of liquid smoke production, product packaging, and opportunities for selling liquid smoke as biopesticides organic among the farmers. Recent conclusion of this community capacity building has been increasing knowledge among farmers from 20.3% to 57%. Through the assistance, the group of production biochar center was empowered become center of input agricultural such as biopestisida and biochar.